Education and youth labour market outcomes : the added value of VET - Flisi, Sara [Verfasser]; Goglio, Valentina [Verfasser] (Publications Office of the European Union, 2015)
"The systematic inclusion of information on orientation of study (vocational vs. general) in the Labour Force Survey (LFS) starting from 2014 will give the possibility to analyse the features and the labour market outcomes of individuals depending on the programme orientation of their qualification. One of the main purposes of this technical briefing is to investigate the possible impact of the addition of this information in the context of the Joint Assessment Framework (JAF) approach, in particular with reference to the benchmark on the employment rate of recent graduates. In this perspective, orientation of study appears to be a natural candidate for inclusion among the additional sub-groups concerning the employment rate of recent graduates within the JAF methodology. The analysis carried out in the briefing shows a labour market advantage, at least in the short run, of young individuals with VET qualifications (compared to their non-VET counterparts), although with important cross-country differences. However, in the context of the JAF approach, the current data availability would not allow programme orientation to work in the same way as other JAF sub-groups, thus the recommendation is to add the VET/non-VET distinction within one of the sub-groups of the benchmark, i.e. the already existing level of education." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; I 2.2 Europa; Junger Erwachsener; Bildungsniveau; Qualifikationsniveau; Qualifikationsverwertung; Ausbildungsertrag; Statistik; Europa